Methods and compositions for diagnosis and treatment of influenza (2006)
The invention provides method and compositions for determining the presence and amount of an influenza virus in a sample including high risk strains of Influenza A. Also provided are methods for determining whether a subject is infected with a influenza virus, as well as, the type and strain of the influenza virus. The methods involve contacting a sample from the subject with a PDZ polypeptides (PDZ) and/or PDZ ligands (PL) and determining whether binding interactions occur between PDZ and PL. Assays for identifying anti-viral agents are also provided, as well as, methods for using the compositions to alter PDZ binding to PL in influenza infected cells.